Advanced Power Control Technique for Hybrid Wind-Solar Power GenerationSystem Used in Standalone Application - Syam Prasanth, P. R.; J.L. Sunil (Asian Journal of Electrical Sciences, 2014)
This paper proposes a unique standalone hybrid power generation system, applying advanced power control tech- niques, fed by four power sources: wind power, solar power, storage battery, and diesel engine generator, and which is not connected to a commercial power system. Considerable effort was put into the development of active-reactive power and dump power controls. The result of laboratory experiments revealed that amplitudes and phases of ac output voltage were well regulated in the proposed hybrid system. Different power sources can be interconnected anywhere on the same power line, leading to flex- ible system expansion. It is anticipated that this hybrid power generation system, into which natural energy is incorporated, will contribute to global environmental protection on isolated islands and in rural locations without any dependence on commercial power systems.